Structural Inequities, Fair Opportunity, and the Allocation of Scarce ICU Resources - White, Douglas B. (The Hastings Center report, 2021)
The September-October 2021 issue of the Hastings Center Report highlights the important topic of allocating scarce critical care resources during the Covid-19 pandemic. The article by Alex Rajczi and colleagues urges that policy-makers use public reasoning, not private reasoning, when developing triage policies. We completely agree. We show how the allocation framework we developed as private scholars, the “Pittsburgh framework,” has been supported by public reasoning. The article by MaryKatherine Gaurke and colleagues criticizes rationing based on maximizing life-years saved and mistakenly claims that our framework recommended this approach. We explain that our framework never contained such a criterion but instead included a more limited consideration of near-term prognosis. In December 2020, in response to emerging data and important criticisms, we modified our framework to further strengthen equity. We are committed to improving allocation guidelines during crisis standards of care through reflective discussions and debates.